2018
DOI: 10.3389/fnbeh.2018.00081
|View full text |Cite
|
Sign up to set email alerts
|

Aggression in Women: Behavior, Brain and Hormones

Abstract: We review the literature on aggression in women with an emphasis on laboratory experimentation and hormonal and brain mechanisms. Women tend to engage in more indirect forms of aggression (e.g., spreading rumors) than other types of aggression. In laboratory studies, women are less aggressive than men, but provocation attenuates this difference. In the real world, women are just as likely to aggress against their romantic partner as men are, but men cause more serious physical and psychological harm. A very sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
82
2
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(98 citation statements)
references
References 213 publications
(267 reference statements)
5
82
2
4
Order By: Relevance
“…Third, we predicted a positive association between experimental and self‐reported real‐world dyadic aggression (teasing/pranking/creating drama; mutual vs. unilateral) [H3a], and tested whether this relationship varied by age [H3b]. Fourth, we predicted that males would allocate more hot sauce across the network [H4], in line with evidence that males show greater aggression in laboratory tasks (Denson, O'Dean, Blake, & Beames, ).…”
Section: Introductionmentioning
confidence: 87%
“…Third, we predicted a positive association between experimental and self‐reported real‐world dyadic aggression (teasing/pranking/creating drama; mutual vs. unilateral) [H3a], and tested whether this relationship varied by age [H3b]. Fourth, we predicted that males would allocate more hot sauce across the network [H4], in line with evidence that males show greater aggression in laboratory tasks (Denson, O'Dean, Blake, & Beames, ).…”
Section: Introductionmentioning
confidence: 87%
“…The cross-disciplinary interest in the relationship between social status and hormones is not new [14, 1726]. Previous research has demonstrated that hormones, specifically cortisol, progesterone, estradiol (primary in women of reproductive age), testosterone, and the peptide hormone oxytocin, correlate with behavioral traits deemed as “alpha” in women [8, 2635]. For example, attributes including self-assertion, confidence, conceit, forcefulness, control, and willfulness have been associated with higher circulating testosterone levels in women, and lower levels with absence of these alpha traits [28].…”
Section: Introductionmentioning
confidence: 99%
“…Women with high estradiol levels reported fewer competitive interactions in athletics than did other women. Aggression has been associated with high testosterone and low cortisol levels in women [26], as well as negatively associated with estradiol levels [32].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations